The evaluation of the efficiency of horizontal electrotherapy as a factor supporting kinezytherapy in patients with osteoporosis - Janiszewski, Mirosław; Włudyga, Stanisław; Hak, Aneta; Jagier, Małgorzata (Reumatologia/Rheumatology, 2005)
The aim of this paper is a comprehensive evaluation o fan adequately modified horizontal electrotherapy program in women patients with osteoporosis. The patients clinical condition selected organ function indicators and the relationship density changes were taken into consideration. The obtained results indicated a significant increase of bone mass and indicators in patients affects with osteoporosis. Such changes did not occur in patients treated only pharmacologically. The disease was alleviated and the clinical condition of the patients improved. Horizontal electrotherapy can be a valuable supplement of currently applied methods in the treatment of patients with osteoporosis.